Power transition theory: a systematic approach to measuring satisfaction of a rising state with the status quo - Nathan, Mukoma Houtsma (My University, 2022)
Power Transition Theory (PTT) has been in International Relations for more than 50 years and recently saw a resurgence due to the mounting tensions between the US and China. Power transition theory suggests that the international order is structured in a hierarchy, with a dominant power at the top, then great powers underneath it and others below. Once in a while, a great power rises to challenge the dominant power and whether a transition occurs through war or peace, is determined by the rising power level of satisfaction with the status quo. As such, a transition with a dissatisfied great power is most likely to happen through war. While improvement has been made in how the theory measures power, the measurement of satisfaction has vastly remained ad hoc. In its essence, this paper seeks to resolve this problem by proposing a typology of dissatisfaction, namely political dis/satisfaction and economic dis/satisfaction. Moreover, this paper hypothesize that political dissatisfaction is most likely to lead to war than economic dissatisfaction. As such, the focus of this study is to engage in theory development by improving the measurement of satisfaction as a variable in PTT. This discussion happens twofold, primarily through theory building discussion, then through testing it in the UK and US/Germany transition. Lastly, since the US/China transition is of actuality, this paper provides an analysis of this transition in line with the improvement made to the power transition theory
This dissertation is submitted in partial fulfilment of the requirements for the degree of Masters in International Studies to the Faculty of Humanities, University of the Witwatersrand, 2022